Analysis of Factors Influencing Automobile Insurance Premiums in France - Girard, Léa (Journal of Statistics and Actuarial Research, 2024)
Purpose: The aim of the study was to analyze the analysis of factors influencing automobile insurance premiums in France. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Factors influencing automobile insurance premiums in France include vehicle type, driver age, geographical location, claims history, and coverage level. Vehicle type and model affect premiums due to varying risks of theft and repair costs, while younger and less experienced drivers face higher rates. Urban areas generally have higher premiums due to increased traffic and theft risks. Policyholders' claims history and credit scores also impact premiums, reflecting insurers' risk assessments. Unique Contribution to Theory, Practice and Policy: Risk pooling theory, behavioral economics theory & regulatory capture theory may be used to anchor future studies on analyze analysis of factors influencing automobile insurance premiums in France. Implement advanced data analytics and predictive modeling techniques to enhance risk assessment accuracy. Advocate for adaptive regulatory frameworks that balance consumer protection with industry innovation. Policymakers should consider regulatory reforms that promote transparency in premium calculations, standardize risk assessment methodologies across regions, and foster competitive market dynamics.